2012
DOI: 10.3109/14767058.2012.714987
|View full text |Cite
|
Sign up to set email alerts
|

Use and misuse of antibiotics in the neonatal intensive care unit

Abstract: Severe infections represent the main cause of neonatal mortality accounting for more than one million neonatal deaths worldwide every year. Antibiotics are the most commonly prescribed medications in neonatal intensive care units (NICUs) and in industrialized countries about 1% of neonates are exposed to antibiotic therapy. Signs and symptoms of sepsis are nonspecific, and empiric antimicrobial therapy is promptly initiated after obtaining appropriate cultures in order to prevent deleterious consequences. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 18 publications
0
31
0
4
Order By: Relevance
“…We were able to adjust for some variables known to be related to risk of NEC, including gestational age, birth weight, sex, and receipt of antenatal steroids (35-37). However, data were not available about use of H2 blocking agents or duration antibiotic use, both of which have been associated with increased risk of NEC in the ELBW population (36, 38). If these agents were used more often in conjunction with increasing formula use, our cost estimates may not be accurate.…”
Section: Discussionmentioning
confidence: 99%
“…We were able to adjust for some variables known to be related to risk of NEC, including gestational age, birth weight, sex, and receipt of antenatal steroids (35-37). However, data were not available about use of H2 blocking agents or duration antibiotic use, both of which have been associated with increased risk of NEC in the ELBW population (36, 38). If these agents were used more often in conjunction with increasing formula use, our cost estimates may not be accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all ELBW neonates receive empiric antibiotics in the first days following birth (Cotton et al 2009) even though many are not actually infected (Clark et al 2006; Stoll et al 2005). Empiric antibiotic therapy continues to be standard in neonatal intensive care units for preterm infants considered at risk of sepsis as the benefits are widely perceived to outweigh the risks (McGuire et al 2004) although there is growing concern about this practice (Tripathi et al 2012; Tzialla et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…For this reason it has been considered good practice to screen all babies with RDS by performing blood cultures, as well as looking for other evidence of sepsis such as neutropenia or an elevated C-reactive protein and initiating antibiotic therapy whilst awaiting results. This routine antibiotic therapy approach is debatable as there is no evidence to support it and prolonged empiric antibiotics in preterm babies are associated with adverse outcomes including NEC [115,116] . In women who are known to be colonized with group B streptococcus, the risk of early onset sepsis can be reduced by administration of intrapartum antibiotic prophylaxis, although there are concerns about a high risk of bias in published trials and no effect on mortality has yet been demonstrated [117] .…”
Section: Prophylactic Treatment For Sepsismentioning
confidence: 99%
“…At present it would be considered reasonable not to use routine antibiotics in preterm babies with RDS in lowrisk cases such as planned delivery by elective caesarean section. For those who are started on antibiotics, the shortest possible course should be used whilst evidence for absence of sepsis is sought [116,118] . Routine antifungal prophylaxis with fluconazole or nystatin has also been advocated in recent years to reduce the risk of invasive fungal infection in babies <1,000 g birth weight, although the incidence of this complication in most centres is quite low [119,120] .…”
Section: Prophylactic Treatment For Sepsismentioning
confidence: 99%